The Ratings Intellectual - O'Regan, T.; Balnaves, Mark (ANZCA, 2011)
There are key figures in the design and the maintenance of audience ratings that are often unknown to the public, but whose careers have been in assessing, evaluating and innovating ratings systems. They also tend to be the major figures in the auditing of ratings, of mapping changes in the audience with respect to the ratings, and indeed inventing new ratings systems. Gale Metzger in the United States, Tony Twyman in the UK, and Ian Muir in Australia are each key figures in this regard, but there are many more. In this paper the authors provide an historical overview of what we call the ratings intellectual. These intellectuals deal with ratings measurement as a form of knowledge and when crises in the operation of the ratings emerge they have had the highest profile in their solution. At the same time an important role has been played by more public figures who we can call “general ratings intellectuals”. Historically, some independent ratings intellectuals, like Leo Bogart, have had a public profile as public commentators on ratings as a form of social research alongside ratings entrepreneurs such as AC Nielsen and Hooper in the USA and Bill McNair in Australia who published extensively on audience measurement and ratings often as a means of educating their clients and selling their services. Leo Bogart provided a generation of market researchers with a sense of the utility and scope of ratings as a specific and limited form of market research; while entrepreneurs such as Arthur Neilsen and Bill McNair introduced and promoted the concept of the ratings to potential clients and the broader public in the ratings.After the formalisation of auditing functions from the mid-1960s ratings intellectuals increasingly became involved in both the ongoing investigation of the carriage of the ratings and in seeking improvements to its operations. To do this they often, like Bogart, operated outside the ratings companies themselves. Today, though, the ratings intellectual keeps a much lower profile as intellectuals exercising specific expertise within a particular technical domain even though their importance remains. Our principal figure here is Gale Metzger. The authors consider the operation of both personae as constitutive of the operation of modern ratings as a system of thought. It is our contention that the ratings intellectual represented a particular office although this office certainly changes over time. In this paper we are interested in two kinds of ratings intellectuals as distinct personae.